Post phacoemulsification wound infection by Nocardia cyriacigeorgica: a rare acid-fast organism. Issue 11 (9th November 2020) - Rana, Rimpi; Rohilla, Ranjana; Bhatia, Mohit; Gupta, Neeti
Abstract : Tunnel infection is one of the most dreaded infections, post phacoemulsification. Most cases reported till now are caused by Gram-positive and Gram-negative bacteria or fungi and very few cases by the acid-fast organisms. Ocular infections by Nocardia usually have poor prognosis. Here, we report a case of tunnel infection, its management and microbiological identification of cause behind it, that is, Nocardia cyriacigeorgica a rare acid-fast microorganism.